THE EFFECT OF WORK TRAINING AND WORK ETHIC ON TEACHER PERFORMANCE THROUGH WORK MOTIVATION AT STATE VOCATIONAL HIGH SCHOOL 1 STABAT - Murti Khairani Lubis; Kiki Farida Ferine; Yohny Anwar (RADJA PUBLIKA, 2026)
This study aims to analyze the effect of job training and work ethic on teacher performance with work motivation as a mediating variable at State Vocational High School (SMK) 1 Stabat. The background of this study stems from the importance of improving the performance of vocational teachers through strengthening training, work ethic, and work motivation. This study uses a quantitative approach with a population of 89 civil servants at SMK Negeri 1 Stabat (civil servants and PPPK), all of whom were used as samples (population research). Data were collected through a Likert scale questionnaire and analyzed using Partial Least Squares (PLS) with SmartPLS. The results show that job training has a positive but insignificant effect on teacher performance, but has a positive and significant effect on work motivation. Work ethic has a positive and significant effect on teacher performance and work motivation. Work motivation also has a positive and significant effect on teacher performance. Indirectly, job training through work motivation does not have a significant effect on teacher performance, while work ethic through work motivation has a positive and significant effect on teacher performance. The R² value of 0.811 for work motivation and 0.862 for teacher performance shows that the model is able to explain a high proportion of variance in both dependent variables. These findings confirm that work ethic and work motivation are key factors in improving teacher performance, while job training plays a greater role in encouraging work motivation than in directly influencing performance.